Association between filial responsibility when caring for parents and the caregivers overload - Marinês Aires; Duane Mocellin; Fernanda Laís Fengler; Idiane Rosset; Naiana Oliveira dos Santos; Diani de Oliveira Machado; Carolina Baltar Day; Lisiane Manganelli Girardi Paskulin
ABSTRACT Objective: To analyze the association between filial responsibility and the overload of the children when caring for their older parents. Method: Cross-sectional study with 100 caregiver children of older adults. Filial liability was assessed by the attitudes of the responsible child (scale of expectation and filial duty) and by care behaviors (assistance in activities of daily living, emotional and financial support, and keeping company). The overload was assessed by the Caregiver Burden Inventory. To assess the associations, the correlation coefficients of Pearson and Spearman, Kruskal-Wallis Test, and Mann-Whitney were employed. Variables that presented p-value<0.20 in the bivariate analysis were inserted in a multivariate linear regression model. Results: The factors associated with overload were: formal employment (p=0.002), feelings regarding family life (p<0.001), financial support (p=0.027), and assistance with Activities of Daily Living (ADLs) (p<0.001). Conclusion: Children who were more involved with the ADLs and provided financial support showed higher levels of overload.